Bentuk Dan Fungsi Deiksis Dalam Novel Edensor Karya Andrea Hirata Serta Implikasinya Terhadap Pembelajaran Novel Di SMA - Gabriel Pardameans Sitorus; Petrus Poerwadi; Yuliati Eka Asi; Misnawati Misnawati; Nirena Ade Christy (Universitas Palangka Raya, 2023)
This study aims to determine the form and function of deixis in the novel literature found in Edensor by Andrea Hirata. This research focuses on finding elements of persona deixis, time deixis, space or place deixis, and social deixis in Edensor's novel. The main problem under study is to reveal the form and function of deixis in detail in pragmatic studies. The researcher also aims that the results of deixis analysis in the novel Edensor by Andrea Hirata can be implicated in learning novels in high school. This research is a descriptive study using a qualitative approach with the type of research used is content analysis techniques (content analysis). Research with content analysis method is used to obtain information from the data obtained. This method can be used to analyze all forms of communication, such as newspapers, books, films and so on. Thus, the approach and type of research in this study is a descriptive qualitative approach. This study describes the sentences resulting from data analysis in the form of words or phrases in the novel Edensor by Andrea Hirata which have been analyzed in terms of the deixis elements of pragmatic studies. The results of this study found that there are many elements of deixis used in Edensor's novel. The tendency of the deixis elements contained in this novel is persona deixis because the author of the novel tends to bring up characterization elements and then followed by time deixis because it has back and forth flow and spatial deixis because it rarely raises the setting of the place and the least deixis element in this novel is the social deixis element. . Persona deixis in this novel has the form I, you, I, you, you, they, we, he, she, -nya,-mu,-ku,ku-. Then the deixis of time refers to the past, present, and future. Place deixis refers to a place that is far from the speaker, which is close to the speaker, and to which the speaker is going. Then social deixis which refers to social status, social position, and maintaining politeness in speaking.